FAKTOR-FAKTOR PENERAPAN ASI EKSKLUSIF DI SAMARINDA - Zulaikha, Fatma; Ramadhani, Laili (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2017)
Giving exclusive breastfeeding has been influenced by many factors, included mother’s knowledgeand education. This research aim was to analyze factors related to giving exclusive breastfeeding inSamarinda city. This research used correlational method with cross sectional and cluster samplingin 62 mothers who had children with 6-12 months at Loa bakung District Samarinda. The study wasconducted from April to May 2017 used questionaire. Factors which studied were mother’soccupation, education, knowledge and husband support. Analysis result showed that factors relatedto the giving exclusive breastfeedng were knowledge (p=0,007 < 0,05) and husband support(p=0,000<0,05). Husband support factor and knowledge has affected 7 time higher in successful ofgiving exclusive breastfeeding OR= 6,587 (CI 95 %= 3,458- 13,598) for husband support andknowledge OR =6,667 (CI 95% = 0,648 – 68,556).